القاضي الفقيه الحاج الداودي التلمساني الـمتوفى سنة 1271هـ/1854م محطات من سيرته الاجتماعية وجهوده العلمية - لشهب, أحمد (جامعة الوادي - University of Eloued, 2021)
يتناولُ البحث ترجمة أحَدَ أعلام الجزائر، وهو القاضي الفقيه الحاج الدّاوُدي التّلمسانيّ (المتوفّى سنة 1272هـ/1854م)، حيث يستعرض محطّات من حياته الاجتماعيّة، وأضواء عن مرجعيَّته العقديَّة والسُّلوكية ومذهبه الفقهيّ، وإطلالات عن حياته العِلميّة من شيوخ وتلاميذ وتآليف، ومن نتائج البحث علو مكانة المترجم بين علماء عصره، وأثر عطائه العلميِّ الذي ظهر في كثرة العلماء الذين أخذوا عنه. The subject matter of the paper looks after El Hadj Addaoudi Attlemceni (died 1272 AH/1854 AD), a judge, a faqih and one of the Algerian scholars. This paper confronts some stages of his social life, his attitude and belief, his doctrine of jurisprudence as well as an overview regarding his educational life in relation with his teachers, his students and his books. As a result, the paper found that El Hadj Addaoudi has a higher status as compared to the scholars of his time as well as the impact of his teachings represented in the numerous scholars who benefited from him.
Stations from the Biography of The Judge andFaqih El HadjAddaoudiAttlemceni (died 1272 AH / 1854 AD
مقال
Keywords: الحاج الداودي؛ تلمسان؛ المغرب الأقصى; El Hadj Addoudi; Tlemcen; Morocco